2002
DOI: 10.1002/jrs.825
|View full text |Cite
|
Sign up to set email alerts
|

Surface‐enhanced Raman scattering of imidazole adsorbed on an iron surface

Abstract: The adsorption of imidazole on a roughened polycrystalline iron electrode was investigated by the SERS technique at pH values of neutral, 11 and 14 and compared with those from each solution. The results indicated that imidazole was adsorbed as mainly the neutral form and/or a certain amount of ylide form on the Fe surface in a neutral solution. The molecules have maximum adsorption at −0.9 V potential with tilted or perpendicular orientation with respect to the Fe surface, whereas a face-on orientation of imi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 16 publications
2
15
0
1
Order By: Relevance
“…12 The band at 826 cm 1 is assigned to an out-of-plane vibration of CO 2 , CO 2 , following Moreno et al 12 In the range 750-1000 cm 1 it is possible to observe the symmetric stretching vibration of C-C and C-C-N structures. 11 -13 The band at 919/918 cm 1 is assigned to an out-of-plane CH deformation of the imidazole ring, while the bands at 1066/1068 cm 1 are assigned to an in-plane CH deformation of the imidazole ring, following Wang et al 15 The band at 1161/1164 cm 1 is also assigned to a vibration of the imidazole ring, specifically an in-plane NH deformation following Wang et al 15 The bands at 1141 and 1145 cm 1 [y(zz)y and y(zx)y scattering geometries] are assigned to a rocking vibration of NH 3 C , r NH 3 ; in monohydrated L-asparagine the same vibration is observed between 1141 and 1147 cm 1 . 12 The 1264 cm 1 band is assigned to an in-plane HC deformation of the imidazole ring.…”
Section: Assignment Of Bands To Internal Modesmentioning
confidence: 99%
See 1 more Smart Citation
“…12 The band at 826 cm 1 is assigned to an out-of-plane vibration of CO 2 , CO 2 , following Moreno et al 12 In the range 750-1000 cm 1 it is possible to observe the symmetric stretching vibration of C-C and C-C-N structures. 11 -13 The band at 919/918 cm 1 is assigned to an out-of-plane CH deformation of the imidazole ring, while the bands at 1066/1068 cm 1 are assigned to an in-plane CH deformation of the imidazole ring, following Wang et al 15 The band at 1161/1164 cm 1 is also assigned to a vibration of the imidazole ring, specifically an in-plane NH deformation following Wang et al 15 The bands at 1141 and 1145 cm 1 [y(zz)y and y(zx)y scattering geometries] are assigned to a rocking vibration of NH 3 C , r NH 3 ; in monohydrated L-asparagine the same vibration is observed between 1141 and 1147 cm 1 . 12 The 1264 cm 1 band is assigned to an in-plane HC deformation of the imidazole ring.…”
Section: Assignment Of Bands To Internal Modesmentioning
confidence: 99%
“…15 The bands observed at 1315 and 1336 cm 1 are possibly associated with stretching of the imidazole ring. The band at 1360/1365 cm 1 is assigned to a bending of CH, υ(CH), following Moreno et al 12 The two bands at 1450 and 1485 cm 1 can also be assigned to a stretching vibration of the imidazole rings, and the bands between 1600 and 1650 cm 1 are assigned to a stretching vibration of C O, C O , or an asymmetric stretching of CO 2 , a CO 2 , following Wang et al 15 However, the band observed at 1648 cm 1 might instead be assigned to a deformation vibration of NH 3 C , in particular, assigned to NH 3 C asymmetric bending, υ a NH 3 . Two main effects are characteristic of systems with the N-H O bond (or A-H B complexes in general): (i) a wavenumber decrease of the N-H stretching mode; (ii) a wavenumber increase of the N-H deformation mode.…”
Section: Assignment Of Bands To Internal Modesmentioning
confidence: 99%
“…The procedure of roughening the iron surface has already been described in detail elsewhere. 22 The Raman equipment was a confocal micro-Raman spectrometer (Super LabRam II system, Dilor, France). Excitation was effected with 632.8 nm radiation from a 13 mW He-Ne laser.…”
Section: Methodsmentioning
confidence: 99%
“…20,21 In recent years, our laboratories have observed the chemical interaction between imidazole and a pure iron surface using a confocal micro-Raman spectrometer and the SERS technique and acquired stronger Raman signals of the surface adsorbate. 22,23 In this work, benzimidazole (BIMH) and 2-mercaptobenzothiazole (HMBT) were chosen as target molecules to investigate the interaction of organic molecules with elemental iron or iron oxide, these molecules have already been studied in detail on elemental silver and gold, because their nitrogen and sulfur atoms are strong electron donors to iron and iron oxide. Our principal aim was to establish a foundation for future investigations of the interaction of organic molecules with iron or iron oxide nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…We have also reported the SERS spectra of imidazole on an iron surface at various pH values. 12 In this work, two kinds of IP 6 SAMs formed at the iron surface at pH 5 and 11.27 were examined using the surfaceenhanced Raman mapping technique. Furthermore, based on the recorded SERS spectra of IP 6 at the iron surface and quantum chemistry calculations for the vibrations of IP 6 , the adsorption mode of IP 6 was proposed.…”
Section: Introductionmentioning
confidence: 99%